SEARCH FOR THE THIRD HARMONIC OF TYPE III BURSTS RADIO EMISSION AT DECAMETER WAVELENGTHS - Brazhenko, A. I.; Melnik, V. N.; Konovalenko, A. A.; Pylaev, O. S.; Frantsuzenko, A. V.; Dorovskyy, V. V.; Vashchishin, R. V.; Rucker, H. O. (Одеські астрономічні публікації, 2012)
The results of observations of trio bursts consisting of type III bursts are presented in this paper. The instantaneous frequency ratio of trio components is near 1:2:3. We analyze flow, duration, frequency drift rate and polarization of trio components as well as dependencies of these characteristics on frequency.